The impact of the Mobile Legend game in creating virtual reality - Khefti Al Mawalia (Universitas Airlangga, 2020)
Online games have been very popular nowadays, more than games played by children and teenagers 30 years ago. This study aims to explore technological developments that people are interested in, namely the phenomenon of the emergence of the online game Mobile Legend. Mobile Legend has succeeded in making Indonesians interested because of its avatar, message feature, and buying and selling of online characters in one application. The evolution of online games from PC to Smartphone makes it easier for gamers to play games anywhere and anytime. Not infrequently, they can spend up to 6 hours a day looking for internet network access. Researchers use determinism theory to answer this phenomenon. The method in this study uses a qualitative type with a virtual ethnographic method. In addition, this research collects data on using virtual tracing to record and documenting virtual activities, and interviews with seven informants of Mobile Legends' players. This research shows that when a person plays games, he can become more apathetic and minimize interaction and communication with the social environment around him. Technology like Mobile Legend has eroded the socio-cultural side and communication sensitivity of an individual in society. All users also become more active and narcissistic in creating multiple identities that exist in the virtual world. So this research shows that online games in creating virtual reality have both positive and negative impacts on the players.